2012
DOI: 10.1159/000342370
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Single-Dose Fosfomycin as Antimicrobial Prophylaxis for Patients Undergoing Transrectal Ultrasound-Guided Biopsy of the Prostate

Abstract: Turkeytant infections, and all of them occurred after the ciprofloxacin or levofloxacin prophylaxis and none after fosfomycin prophylaxis. Conclusions: The ease of use of fosfomycin, reducing the rate of fluoroquinolone-resistant infections and hospitalizations shows that it would be an alternative and effective drug for antimicrobial prophylaxis in TRUSBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 53 publications
2
50
1
3
Order By: Relevance
“…We registered all episodes of symptomatic UTIs that occurred within 1 month after the procedure. A 1-month interval was chosen to increase the likelihood of capturing all symptomatic UTIs attributable to the prostate biopsy [15]. Data were collected by reviewing all ambulatory and hospital medical charts in case of hospitalization for symptomatic UTIs.…”
Section: Data Collection and Microbiological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We registered all episodes of symptomatic UTIs that occurred within 1 month after the procedure. A 1-month interval was chosen to increase the likelihood of capturing all symptomatic UTIs attributable to the prostate biopsy [15]. Data were collected by reviewing all ambulatory and hospital medical charts in case of hospitalization for symptomatic UTIs.…”
Section: Data Collection and Microbiological Considerationsmentioning
confidence: 99%
“…They found that among all patients with febrile UTI, 5.2 % received prophylaxis with FT while 94.8 % received fluoroquinolonebased prophylaxis [15]. In other words, FT seems to be an effective drug and a valid alternative for antimicrobial prophylaxis in TR-PB [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although fluoroquinolones are the most frequently used agents in prophylaxis, the duration of prophylaxis and the choice of antibiotics should be discussed first (34). It has also been reported that the use of fosfomycin trometamol or prophylactic antimicrobial based on rectal swab is currently being investigated as an alternative to antimicrobial prophylactic agents, meta-analyses are being undertaken, and new recommendations on prophylaxis will be included in guidelines to be published in the following years (38,39,40).…”
Section: • Transrectal Prostate Biopsymentioning
confidence: 99%